2021
DOI: 10.3390/app11146308
|View full text |Cite
|
Sign up to set email alerts
|

Study of Possible Frequency Dependence of Small AC Fields on Magnetic Flux Trapping in Niobium by Polarized Neutron Imaging

Abstract: Reducing the size of ambient magnetic flux trapping during cooldown in superconducting radio-frequency niobium cavities is essential to reaching the lowest power dissipation as required for continuous wave application. Here, it is suggested that applying an alternating magnetic field superimposed to the external DC field can potentially reduce the size of trapped flux by supporting flux line movement. This hypothesis is tested for the first time systematically on a buffered chemically polished (BCP) niobium sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The study of type II superconductors by polarized neutron imaging started first on niobium (Nb), a type II/1 superconductor with a rather low Tc = 9.2 K. The samples were quite large (∼ cm 3 ) and easy to handle [24], [25]. These first measurements were test runs for another sample, La 2−x Sr x CuO 4 (x = 0.09), a superconductor of type-II, which was more interesting because of its higher Tc = 32K and because it was already intensively studied [26], [27], [28].…”
Section: Superconductor Type-iimentioning
confidence: 99%
“…The study of type II superconductors by polarized neutron imaging started first on niobium (Nb), a type II/1 superconductor with a rather low Tc = 9.2 K. The samples were quite large (∼ cm 3 ) and easy to handle [24], [25]. These first measurements were test runs for another sample, La 2−x Sr x CuO 4 (x = 0.09), a superconductor of type-II, which was more interesting because of its higher Tc = 32K and because it was already intensively studied [26], [27], [28].…”
Section: Superconductor Type-iimentioning
confidence: 99%
“…Recent studies have demonstrated that the distribution of the magnetic flux in free space and in materials can be visualized through neutron imaging methods using pulsed polarized neutrons. [15][16][17][18][19][20][21][22] In this method, the total magnetic flux density integrated along the flight path of the neutron can be estimated by analyzing the frequency of the Larmor precession oscillation of a neutron's spin. A time-of-flight (TOF) analysis with pulsed polarized neutrons is a suitable technique to accurately estimate the Larmor precession frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The Beijing imaging group operates a similar bimodal neutron and X-ray instrument as the Swiss group, except that it uses a single-electron linear accelerator and has implemented an interesting alternative to the Swiss instrument with a single-source-one-detector system for both neutrons and photons [7]. Another collaboration between a Canadian and two German Institutes studied the influence of external AC fields on magnetic flux trapping of matter in a superconducting state by polarized neutron imaging [8]. Additionally, from the Berlin University of Applied Sciences, Germany, the problem of determination of the spatial resolution of polarized neutrons was investigated mathematically and experimentally [9].…”
mentioning
confidence: 99%